Competency management / Irzan Ismail - Ismail, Irzan (2003)
Developing human competence is essential to every organization. In an extremely competitive environment, human or employee competence is the most important asset and it can also give a big impact in striving for a better position in the industry. It has also been a major factor in creating trust and building extensively partnerships with most of the world's leading player in different kind of industries. This is why human competence needs to be systematically developed throughout the entire organization, using defined terminology and a competence management process. Managing competence implies staying updated on the present competence situations; defining the needs for tomorrow - link to the strategic plans and scenarios; and continuously taking action to fill competence gaps. It also encompasses the active areas that need to be addressed; competence requirement, present competence, and gaps, plan and actions. Everyone must state his or her goals and objectives that need to be fulfilled. They are responsible for ensuring the right competence to reach these goals, considering the organization's changing needs. This means that they must specify the competence requirements within their operations.